High-cycle-fatigue properties of selective-laser-melted AlSi10Mg with multiple building directions. (15th June 2022) - Zhang, Yucheng; Li, Xiaolong; Yuan, Shihua; Sun, Rui; Sakai, Tatsuo; Lashari, Muhammad Imran; Hamid, Usama; Li, Wei
Highlights: Fatigue strength is related to the microstructure varying with building direction. Subsurface failure is all induced by LoF with larger size at higher building angle. Threshold value and transition crack size drop as building angle increases. A life prediction model with the stress concentration effect of defect is proposed. Abstract: Axial loading fatigue tests with stress ratio of 0 were conducted in investigating the influence of building directions (0°, 45° and 90°) on high cycle fatigue property of a selective laser melted AlSi10Mg in combination with two-dimensional microscope observation and three-dimensional ultra-depth imaging. Results show that fatigue strength decreases with the increase of building angle due to larger defects and sparser melting pool boundaries. Two failure modes, i.e. surface and subsurface failures, are mainly induced by irregular lack of fusion whose size arises as building angle increases. Also, the roughness of crack nucleation region is mainly attributed to the plastic deformation of crack tip under tensile stress. Based on the stress intensity factor evaluation at crack tip, both long crack growth threshold value and transition size from small to long crack growth all drop as building angle increases. Based on these, the microstructure-based crack nucleation and propagation behavior is clarified, and an energy based fatigue life prediction model considering the stress concentration effect of defect is proposed. The agreement between experimental and predicted data is satisfied. Graphical abstract: Image, graphical abstract